Transformative approaches in hemophilia management: from traditional therapies to prenatal stem cell treatment - Kao, Yung-Tsung; Fan, Hueng-Chuen; Ro-Lin Chang, Gary; Chen, Jen-Kun; Yen, Chih-Ching; Sufian, Muhammad; Yang, Shang-Hsun; Chen, Chuan-Mu (Frontiers in Bioengineering and Biotechnology, 2025)
The increased global incidence of hemophilia, along with its concomitant consequences arising from prolonged hemorrhage after an injury and a heightened vulnerability to internal bleeding in joints or the brain, brings to the forefront the development of innovative therapeutic strategies to alleviate this hereditary genetic disorder. Current treatments for hemophilia primarily depend on plasma concentrates; however, their widespread use is constrained by the reliance on blood donations and the associated risk of infections. Alternative protein-based therapeutics, such as recombinant coagulation factors, bypassing agents, and non-factor-based drugs, have been approved and utilized for the prophylaxis and treatment of hemophilia with promising outcomes; yet, their shortcomings consist of the necessity for repeated administration and the likelihood of inhibitor formation. With the emergence of the cutting-edge gene editing (CRISPR/Cas9) and gene delivery (viral and non-viral vectors) techniques, the recent progression in gene therapy, stem cell transplantation, and prenatal interventions via in utero stem cell therapy inspires optimism for individuals afflicted with hemophilia and their families, even though these innovative techniques remain in the preclinical stage with a lot of technical and ethical issues needing to be resolved. This review article provides a comprehensive overview of hemophilia management, from traditional therapies to advanced prenatal stem cell treatments, highlighting the evolution and future directions in addressing this genetic bleeding disorder.